Stratigraphic data and physical properties of IODP Site U1451 - Weber, Michael E (PANGAEA, 2023)
Here, sediment-physical properties of the Bengal Fan IODP Expedition 354 are tabulated in support of the paper by Kawsar et al. (2023). This comprises color reflectance data L*, wet-bulk density, magnetic susceptibility, and natural gamma radiation for Supplementary Figure 3. For methods see (Weber et al., 1997). For the Age depth model, low-resolution age control for Site U1451A is tabulated for biostratigraphy with 15 first occurrences (FO) and last occurrences (LO) of species datums, their depth distribution and depth uncertainty according to the age scale of Gradstein (2012). Low-resolution age control provided by 12 magnetostratigraphic reversals with depth. All data from species datums and magnetostratigraphic reversals are from (France-Lanord et al. (2016). Additional biostratigraphic data are from Blum et al. (2018) with depth, age and age error. The resulting high-resolution depth-age model based is given in dataset doi:10.1594/PANGAEA.964099. It relies on tuning color reflectance L* to insolation at 20°N for the month of June using the orbital solutions of Laskar et al. (2004). Note that the top 32 tuning points (0-83.44 m; 0-1.208 Ma) are from Weber and Reilly (2018) and the remaining 138 tuning points below (89.46-367.5 m; 1.339-8.485 Ma) are from this study. This supplementary data corresponds to Fig. 3 of the paper.
Keywords: Physical properties; Stratigraphy